Discovery of the first PD-1 ligand encoded by a pathogen - Martínez-Vicente, Pablo; Poblador, Francesc; Leitner, Judith; Farré, Domènec; Steinberger, Peter; Engel, Pablo; Angulo, Ana (Frontiers in Immunology, 2022)
Large double-stranded DNA viruses deploy multiple strategies to subvert host immune defenses. Some of these tactics are mediated by viral gene products acquired by horizontal gene transfer from the corresponding hosts and shaped throughout evolution. The programmed death-1 (PD-1) receptor and its ligands, PD-L1 and PD-L2, play a pivotal role attenuating T-cell responses and regulating immune tolerance. In this study, we report the first functional PD-L1 homolog gene (De2) found in a pathogen. De2, captured by a gammaherpesvirus from its host during co-evolution around 50 million years ago, encodes a cell-surface glycoprotein that interacts with high affinity and stability with host PD-1. We also find that mutations evolved by the viral protein result in a significant loss of its ability to interact in cis with CD80, an interaction that for PD-L1:CD80 has been reported to block PD-1 inhibitory pathways. Furthermore, we demonstrate that the viral protein strongly inhibits T-cell signaling. Our observations suggest that PD-L1 homologs may enable viruses to evade T cell responses, favor their replication, and prevent excessive tissue damage. Altogether, our findings reveal a novel viral immunosuppressive strategy and highlight the importance of the modulation of the PD-1/PD-L1 axis during viral infections.